Evaluación de la germinación y crecimiento de plántula de chiltepín (capsicum annuum l variedad glabriusculum.) en invernadero (2011)
Título en ingles: Evaluation of germination and seedling Growth of Chiltepín (Capsicum annuum L variedad glabriusculum)  greenhouse Abstract The chiltepin is one of the natural resources of the sinaloense saw, which reaches a commercial value of $100.00 mexican pesos  for 250 g approximately, due to the fact that its crop implies penetrating in the low caducifolia jungle and crossing kilometeres to be able to obtain it, in addition the persons of the region who collect it obtain the resource of an irrational way extracting the plant in its entirety from the root, which causes a minor production in the following season of crop. Due to the fact that it is a native plant of the highland region and that the conditions of germination of the seed are achieved when the fruit is consumed by birds and passes for its digestive tract, it is a plant difficult to cultivate. By what preliminary studies were realized to evaluate the germinative percentage of the plant of chiltepín. There was placed to the shade for one month a whole of 2 000 seeds distributed in 4 charolas by 500 seeds each one. To stimulate the germination the hormone of growth was used giberelina. The beginning of the germination was observed to 8 days, reaching a month an average height of 6.5 cm. The percentage of germination that was reached under these conditions is 97 % (in other studies it has been achieved to obtain in the laboratory up to 57 % of germination), which indicates that in the laboratory it is feasible to cultivate it in a favorable way. It is necessary to realize researches related to the growth, development and establishment of the culture of chiltepín to generate in the region economic resources that derive from this activity. Key words: Giberelic acid; Capsicum annuum L.;  Germination; Chiltepín; natural. Resumen El chiltepín es uno de los recursos naturales de la sierra sinaloense, el cual  alcanza un valor comercial de $100.00 pesos mexicanos por 250 g aproximadamente,  ya que su cosecha implica internarse en la selva baja caducifolia y recorrer kilómetros para poder obtenerlo, además las personas de la región que lo colectan lo obtienen   sin ninguna técnica, pues extraen  la planta en su totalidad desde la raíz, lo que ocasiona una menor producción en la siguiente temporada de cosecha. El chiltepín es difícil de cultivar,  debido a que es una planta nativa de la región serrana y a que las condiciones de germinación de la semilla se logran cuando el fruto es ingerido por aves y pasa por su tracto digestivo. Por ello  se realizaron estudios preliminares para evaluar el porcentaje germinativo de  esta planta. Se colocaron a la sombra, por un mes, un total de 2 000 semillas, distribuidas en 4 charolas con 500 semillas cada una. Para estimular la germinación se empleó la hormona de crecimiento giberalina. El inicio de la germinación se observó a los 8 días, alcanzando al mes una talla promedio de 6,5 cm de altura. El porcentaje de germinación que se alcanzó bajo estas condiciones  fue de 97%  (en otros estudios se ha logrado obtener en el laboratorio hasta un 57% de germinación), lo cual indica que en el laboratorio es factible cultivarlo de manera favorable. Es necesario realizar investigaciones relacionadas con el crecimiento, desarrollo y establecimiento del cultivo de chiltepín para generar en la región recursos económicos que deriven de esta actividad.   Palabras clave: ácido giberélico; chiltepin (Capsicum annuum L. var aviculare);  germinación; chiltepín; natual.